Fear or agitation as normative elements of legitimate self-defence excess (Ius Novum, 2024)
The authors of this publication have explored the importance of justifying fear and agitation underpinning the transgression of necessary self-defence. According to Article 25 § 2 and 3 of the Criminal Code, they identified five scenarios, differing in how a perpetrator’s mental state is determined, affecting the criminal law consequences of unlawfully infringing on or exposing the aggressor’s legal interests. The authors validated the preliminary hypothesis that the legislator assumed legitimate self-defence excess results from fear or agitation due to the circumstances of the assault, necessitating procedural confirmation. Their occurrence leads to the defender’s impunity, regardless of the type of legal interests infringed and the extent of legitimate self-defence excess. A shortfall in the mental state circumstances of a defender, as referred to in Article 25 § 3 of the Criminal Code in a specific factual state, opens the possibility of applying a general, complementary provision, i.e., Article 25 § 2.